Engaging Leadership Reduces Quiet Quitting and Improves Work Engagement: Evidence from Nurses in Greece - Ioannis Moisoglou; Aglaia Katsiroumpa; Ioanna V. Papathanasiou; Olympia Konstantakopoulou; Maria Katharaki; Maria Malliarou; Konstantinos Tsaras; Ioanna Prasini; Maria Rekleiti; Petros Galanis (Nursing Reports)
Background: The leadership style employed by those in positions with authority could significantly impact employees’ work behavior, either positively or negatively. Objectives: The aim of the study was to examine the impact of engaging leadership on quiet quitting and work engagement among nurses. Methods: A cross-sectional study was conducted in Greece with a convenience sample. Data collection occurred throughout October 2024 via an online survey. We utilized Google forms to create an online version of the study questionnaire, which was subsequently shared in Facebook groups for nurses. We used validated tools to measure our study variables, namely, the “Engaging Leadership Scale-12” for engaging leadership, the “Quiet Quitting Scale” for quiet quitting, and the “Utrecht Work Engagement Scale-3” for work engagement. We applied univariate and multivariable linear regression analyses to identify the association between engaging leadership, quiet quitting, and work engagement. p-values less than 0.05 were considered statistically significant. Results: Our multivariable models showed a negative association between engaging leadership and quiet quitting. Moreover, we found a positive association between engaging leadership and work engagement after the elimination of confounders. Conclusions: Our findings suggest that higher levels of engaging leadership reduce quiet quitting and improve work engagement. Nurses’ managers should adopt engaging leadership to improve nurses’ motivation and, thus, clinical outcomes.